The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2147/idr.s219635
|View full text |Cite
|
Sign up to set email alerts
|

<p>CP-CRE/non-CP-CRE Stratification And CRE Resistance Mechanism Determination Help In Better Managing CRE Bacteremia Using Ceftazidime–Avibactam And Aztreonam–Avibactam</p>

Abstract: PurposeThis observational study aimed to identify the independent risk factors for both the acquisition and mortality of carbapenemase-producing carbapenem-resistant Enterobacteriaceae (CP-CRE) bacteremia and further assess the in vitro antimicrobial activities of ceftazidime–avibactam (CAZ/AVI) and aztreonam–avibactam (ATM/AVI) against recent CRE bacteremic isolates.Patients and methodsThis observational study was conducted to reveal the risk factors and mortality rate for CP-CRE bacteremia between 2012 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
4
22
1
Order By: Relevance
“…The synergy among CAZ, ATM and AVI is encouraging and deserves further exploration. In this study, we likewise con rmed the emergence of both CAZ-AVI-resistant and ATM-AVI-resistant S. maltophilia strains isolated from patients without previous antimicrobial exposure to CAZ-AVI and ATM-AVI, which are consistent with our previously ndings that demonstrated CAZ-AVI resistance in the carbapenem-resistant Enterobacteriaceae (CRE) bacteremia isolates from patients with no history of previous CAZ-AVI exposure [18].…”
Section: Bactericidal Activities Of Caz/avi and Atm/avi Against S Masupporting
confidence: 91%
“…The synergy among CAZ, ATM and AVI is encouraging and deserves further exploration. In this study, we likewise con rmed the emergence of both CAZ-AVI-resistant and ATM-AVI-resistant S. maltophilia strains isolated from patients without previous antimicrobial exposure to CAZ-AVI and ATM-AVI, which are consistent with our previously ndings that demonstrated CAZ-AVI resistance in the carbapenem-resistant Enterobacteriaceae (CRE) bacteremia isolates from patients with no history of previous CAZ-AVI exposure [18].…”
Section: Bactericidal Activities Of Caz/avi and Atm/avi Against S Masupporting
confidence: 91%
“…The synergy among CAZ, ATM and AVI is encouraging and deserves further exploration. In this study, we likewise con rmed the emergence of both CAZ-AVI-resistant and ATM-AVI-resistant S. maltophilia strains isolated from patients without previous antimicrobial exposure to CAZ-AVI and ATM-AVI, which are consistent with our previously ndings that demonstrated CAZ-AVI resistance in the carbapenem-resistant Enterobacteriaceae (CRE) bacteremia isolates from patients with no history of previous CAZ-AVI exposure [19].…”
Section: Microbiological Characteristics and Antimicrobial Susceptibisupporting
confidence: 91%
“…18 Similarly, since the first description of China NDM-1-producing strain in 2010, the bla NDM gene has been recovered from various regions in China and been found in the various species of Enterobacteriaceae, including E. coli, K. pneumoniae, E. cloacae, K. oxytoca, E. aerogenes, and C. freundii. 18,19,22 Avibactam is a non-β-lactam-β-lactamase inhibitor that inhibits the activities of Ambler class A -lactamases (eg, ESBLs, KPC), class C β-lactamases, and some class D βlactamases, and avibactam restores the in vitro activity of both ceftazidime and aztreonam against KPC-producing K. pneumoniae isolates, including, in the case of ATM/ AVI, activity against isolates that coproduced MBLs, and avibactam in combination with ceftazidime or aztreonam has the potential to be an agent to treat infections caused by multidrug-resistant bacteria producing the groups of βlactamases compared with piperacillin-tazobactam and other agents. 13,16,17 In addition, our results are similar to those of studies previously reported for the action of avibactam.…”
Section: Discussionmentioning
confidence: 99%